The Wise Leader's Compass - Ethical Leadership for Success : Incl. Bonus - Ethics, Wisdom and Modern Leadership, How Value-Based Leadership Creates Sustainable Success. - Janson, Simone; ProQuest (firma) (Duesseldorf : Best of HR - Berufebilder.de, 2026)
Also in the 4th revised and improved edition, published by a government-funded publisher involved in EU programs and a partner of the Federal Ministry of Education, you receive the concentrated expertise of renowned experts (overview in the book preview), embedded in an integrated knowledge system with premium content and 75% advantage.
Description based on publisher supplied metadata and other sources.
Part of the metadata in this record was created by AI, based on the text of the resource.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2026. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Corporate culture; Leadership; elektronické knihy; electronic books